Towards Katherine Behar (Ed.), Object-Oriented Feminism - Panayotov, Stanimir (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Stanimir Panayotov Title (English): Towards Katherine Behar (Ed.), Object-Oriented Feminism Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 194-202 Page Count: 9 Citation (English): Stanimir Panayotov, “Towards Katherine Behar (Ed.), Object-Oriented Feminism,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 194-202.